Evaluasi Powder Factor terhadap Jarak Lemparan Flyrock dengan Teori Ebrahim Ghasemi pada Hasil Peledakan di PT Bukit Baiduri Energi Provinsi Kalimantan Timur - Perdi Perdi; Lucia Litha Respati; Albertus Juvensius Pontus; Revia Oktaviani; Tommy Trides (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Blasting activities in coal mining are carried out to fragment overburden material and improve excavation efficiency. However, blasting operations may generate environmental impacts, one of which is flyrock, which can endanger equipment, facilities, and personnel. This study aims to evaluate the influence of blasting geometry and powder factor on flyrock distance and to compare actual flyrock distances with predictions using the Ebrahim Ghasemi method at PT Bukit Baiduri Energi, East Kalimantan. The research was conducted through direct field measurements of blasting geometry parameters, including burden, spacing, stemming, free-face burden, and hole depth from 30 blasting events. The results showed that the actual flyrock distance had an average value of 25.37 m with a maximum distance of 47.01 m, while the Ebrahim Ghasemi prediction method produced an average distance of 24.70 m with a maximum distance of 40.80 m. Correlation analysis indicated that powder factor was the most influential parameter affecting flyrock distance, with a correlation coefficient (r) of 0.93 and a coefficient of determination (R²) of 0.8664, indicating a very strong relationship. An increase in powder factor tends to increase the flyrock distance. Therefore, proper control of blasting geometry and powder factor is essential to minimize flyrock risk and improve blasting safety.